Evaluation of the Sino-American Intellectual Property Agreements: A Judicial Approach to Solving the Local Protectionism Problem - Li, Yiqiang (Columbia Journal of Asian Law, 1996)
Intellectual property protection is a controversial topic in trade negotiations between the United States and China. In principle, China recognizes intellectual property rights (“IPR”) and offers extensive protection for owners through its comprehensive patent, trademark, and copyright laws. But spotty enforcement of these laws in practice has seriously undermined the interests of many foreign investors. Due to strong economic pressures exerted by the United States on China to strengthen its actions against infringing activities, the two countries entered into the 1995 Agreement Regarding Intellectual Property Rights (“1995 Agreement”), followed by an agreement embodied in an exchange of letters between the United States and the PRC in 1996 (“1996 Agreement”). The 1995 Agreement outlines four enforcement mechanisms. The most extensive one establishes an administrative network of provincial, regional, and local administrative agencies and the Intellectual Property Working Conference (“IPWC”), a special body created to assist their work. The main office of the IPWC functions as the central administrative authority primarily responsible for policy-making, while its regional offices formulate plans for actions against infringing operations that take place in more than one jurisdiction. The enforcement authority of each jurisdiction must handle factory raids, arrests, and subsequent prosecutions as requested. Each enforcement authority is comprised of regional branches of administrative agencies overseeing intellectual property protection, such as the Copyright Administration, the Administration for Industry and Commerce (“AIC”), the Patent Office, and the Public Security Bureau.